Relationship of forest survey parameters with indicators of condition in pine protective stands - A. V. Dancheva; S. V. Zalesov; V. S. Korovina (Сибирский лесной журнал, 2023)
The results of a study of the relationship between forest survey indicators and a condition indicators with the size of trees in diameter and their relative height are presented with the possible use of the latter in assessing the state of even-aged, high-density, pure composition pine forest stands of Zatyumenskiy ecological park in the city of Tyumen. It has been revealed, that 6–13 % of the total number of trees in the sample plots falls on the share of small-diameter trees. At the same time, the timber stock of such trees does not exceed 4 % of the total growing stock. Large-diameter trees account for 18–36 % of the total number of trees and 30–50 % of the total timber stock in the sample plots. In terms of indicators such as tree health and relative vitality, relative height and growth stress coefficient, small diameter trees, in most cases, are characterized as severely weakened, dying and biologically unstable. At the same time, large and medium-sized trees are considered as healthy or weakened, but biologically stable. The average indicators of the general state of the tree stand are significantly negatively affected by the presence of small-diameter trees, in most cases, very weakened and dying. A general pattern of deterioration in the state of the tree stand with an increase in recreational impact has been revealed. It has been established that weakened trees with a relative height H/D > 100 are characterized by the smallest diameters, and their number and timber stock increase with an increase in recreational impact. Based on the results of the studies, a number of forestry measures have been proposed to increase the biological stability, recreational attractiveness and protective functions of the studied pine forests.